IT Curriculum for Boot Camp: An Iterative Development In Applying OBE In Computer Science Education for Non-Formal Institution - Tony Wibowo; Julia Veronica (Universitas Pendidikan Ganesha, 2022)
With the development of technology in software design, computer programming is now prevalent in almost every aspect of modern business and daily life. A renewed focus on programming education is attracting workers’ attention and converting skills. In previous research, researchers found difficulties encountered while learning programming languages. In this study, we conduct a case study on Teknokasi startup to develop a curriculum based on customer satisfaction. In this study, data was collected through surveys, which is a qualitative method. The methods used to collect data are interviews and questionnaires. The results of this study indicated three iterations, and further research is required to improve curriculum development. In this iteration, we will use the scrum framework and OBE as a theoretical base. Using input from mentors and students, this study was able to develop the next curriculum and improve programming skills, especially targeted Javascript expertise in a short time frame. Further studies need to be performed to assess this curriculum's effectiveness.